The sustainable development of eco-industrial parks affecting the satisfaction of the map ta phut industrial estate community - Jarin Jarusen; Ekkapong Cheunkamon (Sustainable Futures)
Current environmental problems are almost entirely caused by human actions. Communities near industrial areas cause and experience toxic effects and competition to use the remaining resources, creating societal conflicts. These problems can be solved if everyone in the community joins in seriously preventing and resolving them. Cooperation in solving problems in all sectors will be able to restore natural resources and the local environment to their original state. This study aims to analyse the satisfaction of people in Eco-industrial Parks (EIPs), specifically the communities surrounding the Map Ta Phut Industrial Estate. A self-administered questionnaire was administered to collect data from 607 participants. We collected data and used exploratory factor analysis, confirmatory factor analysis, and structural equation modelling to determine the causal relationship between factors affecting satisfaction. The study results showed that factors relevant to EIP management, including physical, economic, environmental, social, and managerial performance, affect satisfaction. This study also found that Environmental Performance positively affected Social and Economic Performances. Social Performance positively affects Economic Performance. The findings provide actionable insights for industrial estate managers to enhance EIP governance aligned with community satisfaction. Policymakers can use the results to design balanced sustainable development strategies. Community leaders may leverage the evidence to promote participatory decision-making. These outcomes highlight the need for cross-sector collaboration in advancing sustainable eco-industrial urban development.